Macroscopic Dynamic Characteristics and Microscopic Simulation of Round Gravel Under Cyclic Loading - MA Shaokun; TIAN Fapai; HUANG Haijun; MA Min; HE Benfu; DUAN Zhibo (工程科学与技术)
A series of saturated undrained dynamic triaxial tests are conducted using the DYNTTS large-scale triaxial cyclic test system, and a discrete element (DEM) undrained dynamic triaxial model is established based on indoor experiments to explore the evolution of macroscopic dynamic properties and the internal microstructural dynamic response of round gravel under subway cyclic loading. The macroscopic dynamic characteristics of the round gravel and the internal microscopic parameter response law under different relative densities, confining pressures, and dynamic stress amplitudes are analyzed. The results show that when the confining pressure is small (σ3=100 kPa) and the relative density is low (Dr=0.3), the accumulated plastic strain of the round gravel is too large (greater than 0.61%), posing a severe safety hazard for train operation. When the confining pressure is higher (σ3=200, 300 kPa), the cumulative plastic strain is smaller (less than 0.14%), indicating relatively safe train operation. The greater the relative density and confining pressure, the lower the cumulative plastic strain of the specimen, the higher the resilient modulus, and the lower the energy consumption inside the specimen. Therefore, extrusion measures such as high-pressure grouting are considered to improve the relative compactness of the soil to reduce the settlement of the subway foundation. During the cyclic loading process, both the coordination number and anisotropy change periodically. The direction of change in coordination number is opposite to that of cyclic loading, while the direction of change in anisotropy aligns with cyclic loading. With the increase in relative density and confining pressure, the coordination number becomes larger and the anisotropy becomes weaker. With the increase in dynamic stress amplitude, the coordination number decreases and the anisotropy increases. The strong contact is mainly controlled by the axial stresses, which play a significant role in bearing capacity. The research results provide a reference for the design and safe operation of subway lines on round gravel foundations.